Liposomes Co-encapsulating Anticancer Drugs in Synergistic Ratios as an Approach to Promote Increased Efficacy and Greater Safety - Franco, Marina S.; Oliveira, Mônica C. (Anti-Cancer Agents in Medicinal Chemistry, 2019)
The era of chemotherapy began in the 1940s, but it was in the 1960s that it was seen as really promising when the first patients with childhood acute lymphoblastic leukemia were cured with combination chemotherapy. Today, it is known that due to resistance to single agents, combination therapy is essential for tumor eradication and cure. In the last decade, studies have shown that anticancer drug combinations can act synergistically or antagonistically against tumor cells in vitro, depending on the ratios of the individual drugs forming the combination. From this observation and facing the possibility of maintaining the in vivo synergistic ratio of combinations came the idea of co-encapsulating anticancer agents in nanosystems. In vivo studies validated this idea by showing that the co-encapsulation of anticancer agents in liposomes allows the maintenance of drug ratios in the plasma and the delivery of fixed drug ratios directly to tumor tissue, leading to a better efficacy compared to the administration of the free drugs combination. Liposomes co-encapsulating irinotecan/floxuridine are now in Phase II trial, and liposomes co-encapsulating cytarabine/daunorubicin were recently approved by the FDA for treatment of patients with acute myeloid leukemia.
Keywords: co-encapsulation